Advanced characterisation of internal diesel injector deposit molecular compositions - Lamb, Joseph (2022)
Diesel engines remain widely used in a range of applications throughout the world, the clean operation of which is imperative for minimising their environmental impact during the transition towards a decarbonised energy system. The negative impact of insoluble internal diesel injector deposit (IDID) formation on emissions is well documented, and their incidence and severity has increased over the past two decades due to reasons thought to include the higher temperatures and pressures of newer injector systems and the uptake of biodiesel blending. Prevention and mitigation of such deposit formation requires an understanding of the formation process which requires the identification of detrimental fuel and additive components, their mechanisms of contributing to deposit formation, and how new mitigation strategies could prevent them.